Delayed Versus Same-Day Percutaneous Nephrolithotomy in Patients With Aspirated Cloudy Urine - Etemadian, Masoud; Haghighi, Ramin; Madineay, Ali; Tizeno, Adel; Fereshtehnejad, Seyed Mohammad (Urology Journal, 2009)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!–[if gte mso 10]> <![endif]–> Introduction: We present our experience in continuing percutaneous nephrolithotomy (PCNL) versus delayed PCNL when purulent fluid is aspirated during access to the pyelocaliceal system. Materials and Methods: This randomized controlled study was carried out on patients who had purulent urine in the pyelocaliceal system at the initial puncturing during PCNL. Patients with recent untreated urinary tract infection, thick or foul pus in aspirated urine, fever, and immunocompromised condition were excluded. Thirty-one patients were randomly divided into 2 groups. In group 1, PCNL was continued, but in group 2, nephrostomy tube was placed and PCNL was performed 10 days later after documented sterile nephrostomy urine. The preoperative and postoperative findings were compared. Results: There were 16 and 15 patients in groups 1 and 2, respectively. All patients had negative urine cultures for microorganisms, preoperatively. The purulent aspirated fluid was infected in 43.8% and 40.0% of the patients in groups 1 and 2, respectively. Postoperative fever was seen in 25.0% and 26.7% of the patients, respectively. No statistical differences were observed between the two groups in terms of bacteriuria, bacteremia, positive calculus cultures, or stone-free rates, and duration of hospitalization between groups 1 and 2, respectively. More analysis with linear regression model showed that postoperative positive blood culture (P < .001), fever (P = .001), and postoperative positive urine culture (P = .02) correlated with duration of hospitalization. Conclusion: In the absence of untreated recent UTI and aspiration of thick or foul pus, continuing PCNL can be safe while purulent urine is encountered.